Conic Optimization, with Applications to (Robust) Truss Topology Design - Roos, C.; Chaerani, D. (Journal of Mathematical and Fundamental Sciences, 2019)
After a brief introduction to the field of Conic Optimization we present some interesting applications to the (robust) trus topologr design (TTD) problem, where the goal is to design a truss of a given weight best able to withstand a set of given loads. We present a linear model for the single-load case and semidefinite models for the multi-load and the ro' bust TTD problem. All models are illustrated by examples. It is also shown that by using duality the size of some of these models can be reduced significantly.